Answer:
The two consecutive positive integers are
and
.
Explanation:
Let
be an even integer, then the next even integer is
.
The sum of the squares of these even integers is
.
We can write the following equation and solve for
.
.
We expand to get,
.
We simplify to get,
.
This gives us,
![2x^2+4x-48=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9q3ims9als5o11ph81gxxumspr9hu5w1uu.png)
We divide through by 2 to get,
.
This is now a quadratic trinomial
We split the middle term to get,
.
We factor to obtain,
![x(x+6)-4(x+6)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/62udqjxo8mwimu6m27fzvdvwhhtonjjtyi.png)
![\Rightarrow (x+6)(x-4)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wo32f1xw4wz45ovjibjgx1kre71emz8cew.png)
![\Rightarrow (x+6)=0 or (x-4)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/egvjxlyzkw2y1trcw6uojxe1hw07mrp313.png)
![\Rightarrow x=-6 or x=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dkb0qu2o03y06nvb264fak9owp1oso5q9s.png)
We discard
since it is not a positive integer.
![\therefore x=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zgehtevijx8jk0y6uj4by2m5lfyly9vu4r.png)
Hence the two consecutive positive even integers are,
![4](https://img.qammunity.org/2020/formulas/mathematics/high-school/oakq838pf9bgih97nun8e8xbvxcppkdp22.png)
and
![4+2=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/w9auew0pp3ndeilbzta2la6h7twem8rlot.png)